Reflective Practice in Nursing - Howatson-Jones, Lioba (Los Angeles : Learning Matters, 2016)
Reflection enables making sense of, and learning from, experiences that can sometimes seem uncertain, chaotic or even mundane. This book introduces student nurses to reflection in a clear and practical manner. It shows different ways of using reflection to learn and develop as a practitioner, including exploring personal experiences.
Previous edition: 2013.
Includes bibliographical references and index.
Keywords: Nursing; Reflective learning; Critical thinking; Health and Wellbeing